(untitled) (Research, Society and Development, 2020)
This study aimed to record the traditional use of Eleutherine plicata Herb. by the inhabitants of the Ponta do Urumajó Community, located in the rural area of the municipality of Augusto Corrêa-Pará, presenting scientific data that corroborate popular use; in addition to recording the community’s living and housing conditions. As for the methodological aspects, the research took place through a qualitative approach, through field research. The techniques related to data collection processes were: application of free listing, interview, observation, audio / video recording and herbal form. The results reveal that the inhabitants of the community use E. plicata Herb tea. by decoction to combat both diarrhea and amoebiasis, the majority of which depend on this plant as a therapeutic resource. E. plicata Herb. it has chemical compounds, such as: naphthoquinones and isoeleuterine, present in the bulbs of the plant and are probably responsible for the therapeutic action acting against amebiasis. The study corroborates with the scientific literature confirming the validation of local use. It is still necessary to continue with further studies on the active principles of E. plicata Herb.